Tunable Optical Frequency Comb in Semiconductor Microresonator - Kaur, Navpreet (My University, 2021)
Optical frequency comb, a spectrum of equidistant lines, has attracted theoretical and experimental research interest since more than the last two decades. In this thesis work we theoretically generated the optical frequency comb in a dissipative microresonator based on a vertical cavity surface emitting laser (VCSEL). The vertical cavity surface emitting laser is coupled with a saturable absorber and frequency selective feedback. Optical frequency comb has been investigated for different input profiles namely Gaussian, super-Gaussian, sinh-Gaussian and cosh-Gaussian. Both chirped and unchirped profiles have been studied. In all cases optical frequency comb has been generated via cavity soliton formation of the input field. Split-step Fourier transformation based numerical method has been used to find the frequency comb. The generated optical frequency comb from different profiles are then compared. The parametric regions of optical frequency comb generation have been identified for each profile. The possibility of tuning the optical frequency comb has been highlighted.
M.Sc. Thesis
Keywords: Optical Frequency Comb; Cavity Soliton; Saturable Absorber; VCSEL